Inheritance of malate dehydrogenase in wild pepper - SCHUELTER,ADILSON RICKEN (1999)
Leaf extracts from wild pepper (Capsicum flexuosum Sendt) were analysed for the presence of malate dehydrogenase (E.C. 1.1.1.37; MDH) isozymes using starch gel electrophoresis. Seven phenotypes for MDH isozymes were observed in the genitors. Genetic analysis in F1 progenies revealed five loci coding for MDH. Isozyme banding patterns of hybrids indicated that MDH-3 and MDH-4 genes code for monomeric enzymes, while MDH-5 for a dimeric isoform. In MDH-2 loci, one particular F1 progeny showed a significant deviation from the expected isozyme pattern. It is possible that other genes are controlling the expression of MDH-2 in pepper. Also, there are two alleles coding for MDH-2 isozyme. On the other hand, MDH-1 was monomorphic for all genotypes used in the experiment.